Levetiracetam and N-Cadherin Antibody Alleviate Brain Pathology Without Reducing Early Epilepsy Development After Focal Non-convulsive Status Epilepticus in Rats - Avdic, Una; Ahl, Matilda; Andersson, My; Ekdahl, Christine T. (Frontiers in Neurology, 2021)
Focal non-convulsive status epilepticus (fNCSE) is a neurological condition characterized by a prolonged seizure that may lead to the development of epilepsy. Emerging experimental evidence implicates neuronal death, microglial activation and alterations in the excitatory and inhibitory synaptic balance as key features in the pathophysiology following fNCSE. We have previously reported alterations in the excitatory adhesion molecule N-cadherin in rats with fNCSE originating from the hippocampus that subsequently also develop spontaneous seizures. In this study, fNCSE rats were treated intraperitoneally with the conventional anti-epileptic drug levetiracetam in combination with intraparenchymal infusion of N-cadherin antibodies (Ab) for 4wks post-fNCSE. The N-cadherin Ab was infused into the fornix and anterior hippocampus, and immunohistochemically N-cadherin Ab-stained neurons were detected within the dorsal hippocampal structures as well as in superjacent somatosensory cortex. Continuous levetiracetam treatment for 4wks post-fNCSE reduced microglia activation, including cell numbers and morphological changes, partly decreased neuronal cell loss, and excitatory post-synaptic scaffold protein PSD-95 expression in selective hippocampal structures. The additional treatment with N-cadherin Ab did not reverse neuronal loss, but moderately reduced microglial activation, and further reduced PSD-95 levels in the dentate hilus of the hippocampus. Despite the effects on brain pathology within the epileptic focus, neither monotherapy with systemic levetiracetam nor levatiracetam in combination with local N-cadherin Ab administration, reduced focal or secondary generalized seizure frequency, seizure duration, or the amount of interictal activity during one month of continuous electroenephalogram recordings within the hippocampus after fNCSE. Behavioral tests for spatial memory, anxiety, social interaction and anhedonia did not detect differences between fNCSE rats with or without treatment. The results reveal the refractory features of the present rodent model of temporal lobe epilepsy development following fNCSE, which supports its clinical value for further therapeutic studies. We identify the persistent development of epilepsy following fNCSE, in spite of partly reduced brain pathology within the epileptic focus.